Retinotomy with retinal turnover to remove subretinal membranes under direct visualization for proliferative vitreoretinopathy - Kimura M (Dove Medical Press, 2012)
Masayo Kimura,1 Akira Nishimura,1 Yoshiaki Saito,1 Hiroko Ikeda,2 Kazuhisa Sugiyama11Department of Ophthalmology and Visual Science, 2Department of Human Pathology, Kanazawa University Graduate School of Medical Science, Kanazawa, JapanPurpose: The purpose of the study was to report the outcomes for cases of proliferative vitreoretinopathy (PVR) that received retinotomy and removal of subretinal proliferative tissue under direct visualization using retinal turnover.Methods: Nineteen eyes with posterior and/or anterior grade C1–12 PVR that had undergone retinotomy and retinal turnover were reviewed. Main outcomes included the retinal reattachment rate, final best-corrected visual acuity (BCVA), postoperative intraocular pressure, extent of retinotomy, and complications.Results: Final retinal reattachment rates with silicone oil tamponade were 100%. The mean logarithm of the minimal angle of resolution (logMAR) BCVA was significantly improved (P = 0.001). Positive correlation was found between the extent of retinotomy and both preoperative logMAR BCVA (r = 0.663, P = 0.002) and postoperative logMAR BCVA (r = 0.619, P = 0.005). There was no correlation between the extent of retinotomy and the change in preoperative and postoperative logMAR BCVA (r = –0.267, P = 0.268). Negative correlation was found between preoperative logMAR BCVA and the change in logMAR BCVA (r = –0.587, P = 0.008). There was no correlation between the extent of retinotomy and the intraocular pressure at the final visit (r = –0.316, P = 0.188). Corneal decompensation due to silicone oil in the anterior chamber occurred in one eye.Conclusion: Removal of subretinal proliferative tissue with retinal turnover seems to be an effective procedure.Keywords: proliferative vitreoretinopathy, retinotomy, retinal turnover, subretinal proliferative tissue, under direct visualization